2016
DOI: 10.1371/journal.pone.0152500
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of Tumor-Infiltrating Lymphocytes in Breast Cancer: A Systematic Review and Meta-Analysis

Abstract: BackgroundThe prognostic values of tumor-infiltrating lymphocytes (TILs) and TILs subsets in breast cancer (BC) are uncertain.MethodsA systematic literature search (MEDLINE, Web of Science, EMBASE, and the Cochrane Library to August 2014) was conducted for studies which met the eligibility criteria. The primary clinical outcome was defined as disease-free survival (DFS), overall survival (OS), and BC-specific survival (BCSS). Random or fixed-effects model was adopted to estimate the summary hazard ratio (HR).R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
177
4
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(196 citation statements)
references
References 50 publications
11
177
4
4
Order By: Relevance
“…For example, Geng et al clarified that patients with high level of CD8 + , CD3 + and CD4 + TILs had better OS, whereas high density of FOXP3 + TILs was an adverse prognostic factor in lung cancer [53]. Mao et al found that CD8 + TILs were associated with improved DFS, while FOXP3+ TILs were associated with reduced DFS in breast cancer [54]. Yao et al reported that high levels of CD8 + and CD3 + TILs had a better prognostic value on OS and DFS, whereas high levels of FoxP3 + TILs had a worse prognostic value on OS and DFS [55].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Geng et al clarified that patients with high level of CD8 + , CD3 + and CD4 + TILs had better OS, whereas high density of FOXP3 + TILs was an adverse prognostic factor in lung cancer [53]. Mao et al found that CD8 + TILs were associated with improved DFS, while FOXP3+ TILs were associated with reduced DFS in breast cancer [54]. Yao et al reported that high levels of CD8 + and CD3 + TILs had a better prognostic value on OS and DFS, whereas high levels of FoxP3 + TILs had a worse prognostic value on OS and DFS [55].…”
Section: Discussionmentioning
confidence: 99%
“…Although TILs have been recognized to have an important role in anticancer immunity (16,26), the method of in vivo 32: 151-158 (2018) 156 evaluating TILs has differed among previous reports, and there is no established methodology for evaluating TILs (11)(12)(13)(14)(15). The methodology using the H-E-stained sections proposed by the International TILs Working Group is simple and easy because it does not involve immunohistochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor-infiltrating lymphocytes (TILs), which reflect the immune status of the host (7), have been reported to correlate with the clinical outcome, including the chemotherapeutic outcome in patients with various types of cancer (8-10). However, the method of measuring TILs has differed among previous reports (11)(12)(13)(14)(15). Recently, a new method of measuring TILs in breast cancer was proposed by the International TILs Working Group, using H-E-stained sections (16).…”
mentioning
confidence: 99%
“…In TNBC, without treatment, the presence of tumor-infiltrating lymphocytes (TILs) is correlated with improved overall survival, increased metastasis-free survival, and decreased distant recurrence [22]. TILs can predict improved pathological complete response (pCR) to neoadjuvant chemotherapy [23]. Additionally, presence of TILs in residual TNBC after neoadjuvant chemotherapy is also prognostic for better metastases-free and overall survival [24].…”
Section: Tumor-infiltrating Lymphocytes In Tnbcmentioning
confidence: 99%